2021
DOI: 10.1021/acsami.1c14387
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electronic Structure of CoP Embedded in N-Doped Porous Carbon Nanocubes Via Ru Doping for Efficient Hydrogen Evolution

Abstract: Designing and synthesizing stable electrocatalysts with outstanding performance for water splitting is an arduous and urgent task. Herein, Ru-anchored CoP embedded in N-doped porous carbon nanocubes (Ru-CoP/NCs) is successfully prepared. The Ru-CoP/NC reveals superior hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) properties and stability under alkaline conditions, and the corresponding overpotentials are 22 and 330 mV at 10 mA·cm–2, respectively. The unique N-doped porous carbon nanocub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…On the other hand, compared with Pt, the range of energy in PtSi becomes broader, owing to the coupling interactions between the Si s/p‐orbitals and metal d‐orbitals, which make the d‐orbitals center downshift away from the Fermi level (Figure 6C,D). [ 41,42 ] Additionally, as shown in Figure 6E, the d‐band center of PtSi model (−3.763 eV) is far from the Fermi level than that of Pt models (−2.638 eV), meaning a lower desorption between PtSi and adsorbed H species, accordingly favoring the HER performance. [ 43,44 ] In other words, the introduction of Si to Pt could weaken the binding energy between Pt and hydrogen atoms, which further promotes hydrogen generation during the HER process.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…On the other hand, compared with Pt, the range of energy in PtSi becomes broader, owing to the coupling interactions between the Si s/p‐orbitals and metal d‐orbitals, which make the d‐orbitals center downshift away from the Fermi level (Figure 6C,D). [ 41,42 ] Additionally, as shown in Figure 6E, the d‐band center of PtSi model (−3.763 eV) is far from the Fermi level than that of Pt models (−2.638 eV), meaning a lower desorption between PtSi and adsorbed H species, accordingly favoring the HER performance. [ 43,44 ] In other words, the introduction of Si to Pt could weaken the binding energy between Pt and hydrogen atoms, which further promotes hydrogen generation during the HER process.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Ruthenium (Ru) is the most inexpensive element among noble metals. , Moreover, Ru possesses a comparable binding for hydrogen (65 kcal mol –1 ) as Pt (62 kcal mol –1 ). Prior investigations suggest that engineering on size, dimension, and composition are effective to optimize the Ru property, for expediting hydrogen generation. Volmer and Heyrovsky processes are the general rate-determining steps for nonacidic hydrogen production, which typically depend on the ability of water dissociation and hydrogen binding, respectively . Henceforth, ration design is desirable to reach high-performance Ru-based HER catalysts.…”
mentioning
confidence: 99%
“…10 Ruthenium (Ru) is the most inexpensive element among noble metals. 13,14 Moreover, Ru possesses a comparable binding for hydrogen (65 kcal mol −1 ) as Pt (62 kcal mol −1 ). 15−17 Prior investigations suggest that engineering on size, dimension, and composition are effective to optimize the Ru property, for expediting hydrogen generation.…”
mentioning
confidence: 99%
“…Therefore, Ru can serve as a promising dopant to modify the electronic structure of electrocatalysts. For instance, Wang et al 61 reported the successful fabrication of the Ru-doped CoP embedded in N-doped porous carbon nanocubes (Fig. 2a–c).…”
Section: Role Of Ru Dopingmentioning
confidence: 99%